An unusual case of primary peritoneal adenocarcinoma - Singh, Rajdave Singh Sadu; Hisham, Muhammad Rahimi Mohamad; Mohammad, Ahmad Tarmizi; Fazle Abbas, Shabbar Husain; Yusoff, Yussra (International Surgery Journal, 2020)
Primary peritoneal adenocarcinoma is sporadic with few cases cited in pre-existing literature. This cancer arises from the peritoneal epithelium lining of the abdomen, which is derived from extra ovarian mesothelium. It generally carries a poor prognosis. The treatment strategies are similar to ovarian serous papillary carcinoma. Report an incidental finding of primary peritoneal adenocarcinoma in a 39-year-old female army personnel, currently undergoing her chemotherapy and thriving. Exploratory laparotomy was done given the incidental finding of a mass on the contrast-enhanced computed tomography scan (CT). The mass was attached to the greater omentum, however, did not invade the mucosa of the transverse colon. Given this, part of greater omentum was removed. The findings of the immunohistochemical studies of the tumour are described within this report. The diagnosis of a primary peritoneal adenocarcinoma, stage II was established as no other primary site were found upon further investigation. The patient was treated with chemotherapy (carboplatin/paclitaxel) which was planned for 6 cycles. Otherwise, the patient had an uneventful postoperative course, is underway her chemotherapy regime and is planned for interim CT study to assess chemotherapy response. To conclude, isolated solitary primary peritoneal adenocarcinoma without peritoneal carcinomatosis, gastrointestinal manifestations and ascites are rare. This case, however, demonstrates the importance of its diagnosis, accurate evaluation and management.